Propolis extract and bovine bone graft combination in the expression of VEGF and FGF2 on the preservation of post extraction socket - Utari Kresnoadi; Louisa Christy Lunardhi; Bambang Agustono (Wolters Kluwer Medknow Publications, 2020)
Aim: To determine the potential of propolis extract and BBG combination on the quantity of fibroblast growth factor 2 (FGF-2), vascular endothelial growth factor (VEGF), and osteoblasts in the preservation of tooth extraction socket on days 3 and 7. Settings and Design: Laboratory in vivo reseach using animal model. Materials and Methods: Fifty-six Cavia cobaya were divided into eight groups containing seven animals in each group. The extraction socket on the lower left incisor was filled with polyethylene glycol (PEG) at a concentration of 2% (Groups I and II) as a control; active materials consisted of propolis extract and PEG (Groups III and IV); active materials consisted of BBG and PEG (Groups V and VI); and active materials consisted of propolis extract, BBG, and PEG (Groups VII and VIII). Then, an examination was done using immunohistochemistry to perform an expression of VEGF, FGF2, as well as histology of osteoblasts. Statistical Analysis Used: The statistical analysis performed using a one-way ANOVA and Tukey's honestly significant difference test. Results: Propolis extract, BBG and PEG had the most significant result related to the formation of FGF2, VEGF, and osteoblasts. Conclusion: The combination of propolis extract with BBG and PEG in socket preservation is effective in increasing the expression of FGF2, VEGF, and osteoblasts.